Effects of weight reduction on body composition, hormone concentrations and physical performance in female track and field jumpers during a preparatory and competition season - Lällä, Sini (2019)
Introduction. Weight reduction is common and generally accepted among obese people, but nowadays also a general practice among athletes. There are many reasons for athletes to reduce weight: to increase physical performance, to compete in a lower weight class or aesthetic reasons. The aim of this study was to follow the effects of a preparatory season (exercise, diet) on body composition, hormonal concentrations and physical performance in female track and field jumpers and follow those variables throughout summer’s competition season.